Overview and expert assessment of off-label use of misoprostol in obstetrics and gynaecology: review and report by the Collège national des gynécologues obstétriciens français. (April 2015) - Marret, H.; Simon, E.; Beucher, G.; Dreyfus, M.; Gaudineau, A.; Vayssière, C.; Lesavre, M.; Pluchon, M.; Winer, N.; Fernandez, H.; Aubert, J.; Bejan-Angoulvant, T.; et al.
Abstract: The literature suggests that misoprostol can be offered to patients for off-label use as it has reasonable efficacy, risk/benefit ratio, tolerance and patient satisfaction, according to the criteria for evidence-based medicine. Both the vaginal and sublingual routes are more effective than the oral route for first-trimester cervical dilatation. Vaginal misoprostol 800 μg, repeated if necessary after 24 or 48 h, is a possible alternative for management after early pregnancy failure. However, misoprostol has not been demonstrated to be useful for the evacuation of an incomplete miscarriage, except for cervical dilatation before vacuum aspiration. Oral mifepristone 200 mg, followed 24–48 h later by vaginal, sublingual or buccal misoprostol 800 μg (followed 3–4 h later, if necessary, by misoprostol 400 μg) is a less efficacious but less aggressive alternative to vacuum aspiration for elective or medically-indicated first-trimester terminations; this alternative becomes increasingly less effective as gestational age increases. In the second trimester, vaginal misoprostol 800–2400 μg in 24 h, 24–48 h after at least 200 mg of mifepristone, is an alternative to surgery, sulprostone and gemeprost. Data for the third trimester are sparse. For women with an unripe cervix and an unscarred uterus, vaginal misoprostol 25 μg every 3–6 h is an alternative to prostaglandin E2 for cervical ripening at term for a live fetus. When oxytocin is unavailable, misoprostol can be used after delivery for prevention (sublingual misoprostol 600 μg) and treatment (sublingual misoprostol 800 μg) of postpartum haemorrhage. The use of misoprostol to promote cervical dilatation before diagnostic hysteroscopy or surgical procedures is beneficial for premenopausal women but not for postmenopausal women. Nonetheless, in view of the side effects of misoprostol, its use as a first-line treatment is not indicated, and it should be reserved for difficult cases. Misoprostol is not useful for placing or removing the types of intra-uterine devices used in Europe, regardless of parity.